2014
DOI: 10.1055/s-0033-1339124
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Asymmetric Michael Addition Reactions with New Chiral Multisite Phase-Transfer Catalysts

Abstract: Highly enantioselective Michael addition reactions of diethyl malonate to various chalcones have been achieved under mild chiral multisite phase-transfer reaction conditions by the successful utilization of 2,4,6-(triscinchoniummethyl)phenyl-1,3,5-triazines as new chiral quaternary ammonium catalysts. This simple asymmetric Michael addition process was found to be quite effective and to obtain Michael adducts with very good yields and enantiomeric excesses.Phase-transfer catalysis is a versatile, well-establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Jew et al demonstrated the high enantioselectivity of a novel trimeric cinchona alkaloid ammonium salt as a phase-transfer catalyst (PTC) in the catalytic asymmetric alkylation of the N-(diphenylmethylene)glycine tert-butyl ester [21]. Later, the C 3 -symmetric cinchona PTC catalyzed asymmetric synthesis of α-amino acids and the highly enantioselective Michael reaction of chalcones and diethyl malonate were performed by Siva et al [22][23][24][25]. Csámpai and co-workers examined the in vitro antitumor activity of acylated mono-, bis-, and tris-cinchona-based amines [26].…”
Section: Introductionmentioning
confidence: 99%
“…Jew et al demonstrated the high enantioselectivity of a novel trimeric cinchona alkaloid ammonium salt as a phase-transfer catalyst (PTC) in the catalytic asymmetric alkylation of the N-(diphenylmethylene)glycine tert-butyl ester [21]. Later, the C 3 -symmetric cinchona PTC catalyzed asymmetric synthesis of α-amino acids and the highly enantioselective Michael reaction of chalcones and diethyl malonate were performed by Siva et al [22][23][24][25]. Csámpai and co-workers examined the in vitro antitumor activity of acylated mono-, bis-, and tris-cinchona-based amines [26].…”
Section: Introductionmentioning
confidence: 99%
“…Jew et al demonstrated the high enantioselectivity of a novel trimeric cinchona alkaloid ammonium salt as phase-transfer catalyst (PTC) in the catalytic asymmetric alkylation of N-(diphenylmethylene)glycine tert-butyl ester [21]. Later, the C3-symmetric cinchona PTC catalyzed asymmetric syntheses of α-amino acids and the highly enantioselective Michael reaction of chalcones and diethyl malonate were performed by Siva et al [22][23][24][25]. Csámpai and co-workers examined the in vitro antitumor activity of acylated mono-, bis-, and tris-cinchona-based amines [26].…”
Section: Introductionmentioning
confidence: 99%